How Form of Discourse on Traditional Games and Music in Overcoming Bullying in Schools - Halim, M; Rofiloza, Rofiloza; Yunaidi, Yunaidi; Syafniati, Syafniati; Zulfahmi, Muhammad (ppjbsip, 2023)
Bullying is a pervasive manifestation of aggressive conduct that is commonly witnessed among pupils in academic settings. A plethora of bullying behaviours are commonly witnessed in academic environments. The objective of this study is to analyse and clarify the discourse framework that can be utilized to tackle the consequences of bullying associated with traditional games and music, in order to alleviate bullying in educational settings. The current study was designed with the aim of utilizing a comprehensive review of existing literature. The current study involved a cohort of 30 individuals who were registered as pupils at a Conventional Art Institution in Padangpanjang, and was conducted in conjunction with a comprehensive review and analysis of relevant literature. The data employed in this investigation were acquired via the distribution of surveys. The results of this study suggest that the integration of traditional games and music into the academic syllabus can be a viable approach to tackle instances of bullying behaviour. It is advisable for educators across all tiers of the educational hierarchy to integrate conventional games into the pedagogical framework as a means of mitigating occurrences of bullying in academic institutions.